Factors Affecting the Behavior of Lung-Tb Patients in Preventing Transmission - Melfa Hotmaida Simanjuntak; Ismail Efendy; Yuniati Yuniati; Indah Anggraini; Thomson Nadapdap (Journal of Community Health Provision, 2022)
The study aims at determining what factors influence the behavior of pulmonary tuberculosis patients in preventing the transmission of pulmonary tuberculosis at the Garoga Health Center, Garoga District, North Tapanuli Regency in 2022. This type of research uses a descriptive analytic survey with a cross sectional design. The population in this study amounted to 48 people, while the sample amounted to 48 people. Data analysis was carried out by univariate, bivariate and multivariate analysis. The results of the chi square test showed that there was a relationship between 7 variables, namely knowledge, using masks, not spitting carelessly, consuming OAT regularly, isolation, PMO and culture had a p-value <α 0.05, meaning knowledge, using masks, not spitting. indiscriminately, taking OAT regularly, isolation, PMO and culture affect the prevention of pulmonary TB transmission at the Karoga health center, and the multivariate test has 6 knowledge variables, not spitting carelessly, consuming OAT regularly, isolation, PMO and culture affect. the results of multiple logistic regression tests shows that the variable consuming OAT regularly is the most dominant with an odds ratio (OR) of 52,990, meaning that it affects the prevention of pulmonary TB 53 times. The conclusion is that the dominant variable that most influences the prevention of pulmonary TB transmission at the Karoga Health Center is consuming OAT on a regular basis. It is recommended for patients with pulmonary TB to comply with all recommendations from health workers, including taking anti-tuberculosis drugs so that pulmonary TB patients can recover from their disease.